Identification of the ALMT gene family in the potato (Solanum tuberosum L.) and analysis of the function of StALMT6/10 in response to aluminum toxicity - Zhang, Feng; Jiang, Sixia; Li, Qiong; Song, Zhiying; Yang, Ying; Yu, Shirui; Nie, Zongyue; Chu, Moli; An, Yanlin (Frontiers in Plant Science, 2023)
Introduction Aluminum (Al)-activated malate transporters (ALMTs) play an important role in the response to Al toxicity, maintenance of ion homeostasis balance, mineral nutrient distribution, and fruit quality development in plants. However, the function of the StALMT gene family in potato remains unknown. Methods and results In this study, 14 StALMT genes were identified from the potato genome, unevenly distributed on seven different chromosomes. Collinearity and synteny analyses of ALMT genes showed that potatoes had 6 and 22 orthologous gene pairs with Arabidopsis and tomatoes, respectively, and more than one syntenic gene pair was identified for some StALMT gene family members. Real-time quantitative polymerase chain reaction (qPCR) results showed differential expression levels of StALMT gene family members in different tissues of the potato. Interestingly, StALMT1, StALMT6, StALMT8, StALMT10, and StALMT12 had higher expression in the root of the potato cultivar Qingshu No. 9. After being subjected to Al3+ stress for 24 h, the expression of StALMT6 and StALMT10 in roots was evidently increased, displaying their decisive role in Al3+ toxicity. Discussion In addition, overexpression of StALMT6 and StALMT10 in Arabidopsis enhanced its tolerance to Al toxicity. These results indicate that StALMT6 and StALMT10 impart Al3+ resistance in the potato, establishing the foundation for further studies of the biological functions of these genes.